Drosophila melanogaster as a model organism in ecotoxicological assessments - Alves, Silviana Patrícia Hilário (2023)
With the constant concern over the environmental problems we are experiencing, it is becoming progressively more important to conduct ecologically relevant toxicity tests. In this context, the use of model organisms to assess environmental challenges has been increasing, especially the use of Drosophila melanogaster, which has emerged as an economical and preponderant model offering valuable information on the ecological and genetic responses after exposure to various contaminants. This work includes a systematic review of the literature on the use of D. melanogaster in ecotoxicological tests. The review contains studies focusing on the impact of pollutants such as metals, pesticides, bisphenols, and pharmaceuticals on Drosophila. The fruit fly responses to these environmental stressors were analysed using behavioural, reproductive, physiological, and biochemical endpoints. The results highlighted the high toxicity of most substances assessed, revealing the need to conduct additional studies that consider natural settings, with dynamic interactions between the various species in the food chain and the effects of prolonged exposure. In addition, it highlights the importance of investigating the molecular and genetic mechanisms underlying the effects observed, as well as the potential for transposition to other organisms, which can improve the assessment of ecological and human health implications. Thus, this dissertation highlights the role of D. melanogaster as a fundamental tool for ecotoxicological evaluation, as well as its integration into future research leading to the application of improved strategies for the mitigation of ecosystem pollution.